Co-occurrence of feline chronic gingivostomatitis and oral squamous cell carcinoma in 4 cats (2014–2024) - Tsugawa, Anson J.; Soltero-Rivera, Maria M.; Goldschmidt, Stephanie; Arzi, Boaz; Kell, Tessa; Hoyer, Naomi; Bell, Cynthia M.; Gao, Hanzhi; Shan, Guogen; Vapniarsky, Natalia (Frontiers in Veterinary Science, 2025)
IntroductionCats with refractory feline chronic gingivostomatitis (FCGS) exhibit chronic oral inflammation despite surgical and medical therapy. Such areas may resemble or be at higher risk for oral squamous cell carcinoma (SCC). Without routine biopsies, occult SCC may remain undiagnosed.ObjectivesThis study investigated the prevalence and potential association of oral SCC occurrence in cats with refractory FCGS.MethodsA retrospective review of cats with refractory FCGS and oral SCC from two veterinary teaching hospitals (2014–2024) was conducted. Cases with histopathologically confirmed FCGS, SCC, or both were included. Data analyzed included signalment, medical history, treatment, clinical findings, and diagnostics.ResultsTwo hundred twenty-one cats with refractory FCGS and 24 cats with oral SCC at the first institution, and 32 cats with refractory FCGS and 16 cats with oral SCC at the second institution, were presented over a 10-year period. Only four cats from both institutions had co-occurrence of FCGS and oral SCC. All affected cats exhibited bilateral proliferative FCGS lesions in the caudal oral cavity and developed SCC within 16–29 months (mean: 22 months). Two of four cats had epithelial dysplasia at FCGS diagnosis. SCC occurrence was significantly, inversely associated with FCGS at one institution (0.9%, ρ = −0.1424, p-value = 0.00035) but not the other (5.88%, ρ = 0.0495, p-value = 0.1947).ConclusionCo-occurrence of FCGS and SCC is rare. While SCC may develop in proliferative FCGS areas, the low occurrence does not establish FCGS as a predisposing factor for SCC.